Diagnóstico, prognóstico e tratamento dos carcinomas de glândulas mamárias de cadelas atendidas no hospital veterinário da UFMG: estudo retrospectivo - Fernanda Camargo Nunes (2015)
Canine mammary neoplasms are the most frequent neoplasms in bitches. Recently, the Consensus for the Diagnosis, Prognosis and Treatment of Canine Mammary Tumors established criteria that provided a guide for the diagnosis, prognosis and treatment of canine mammary neoplasms. Aiming to evaluate the adoption of such criteria, the present study aims to present a collection of clinical, epidemiological and pathological data of canine mammary neoplasms. Data regarding 1238 clinical charts were collected and 84% were classified as malignant neoplasms, subsequently grouped in carcinomas in mixed tumors (CMT), invasive papillary carcinomas, solid carcinomas, micropapillary carcinomas, carcinosarcomas and tubular carcinomas. The carcinoma groups were correlated to prognosis factors such as tumor size, clinical staging, histological type, and different therapeutical protocols with overall survival. Tumor size was associated with shorter overall survival when 3.0cm (p<0.0001). Clinical staging presented a strong impact on overall survival, since mammary carcinomas in advanced clinical staging (T123N01M01) presented shorter overall survival (median of 268 days for stage IV and 261 days for stage V) when compared to early stages, which did not reach the median survival time (p<0.0001). Regarding histological types, CMT and invasive papillary carcinomas did not reach median survival times when compared to the other histological types (p<0.0001). Longer overall survival was associated with chemotherapy treatment, except for patients with solid and micropapillary carcinomas. Bitches diagnosed with CMT in early clinical stages presented a longer overall survival when compared to advanced clinical stages. A less aggressive biological behavior was associated to the CMT, and clinical staging presented important value in determining its biological behavior and therapeutical options for treatment. These findings demonstrate that besides histological type, clinical staging is an important prognostic factor for bitches with mammary carcinomas. Complementary studies, with a larger number of cases are necessary to evaluate the benefit of adjuvante therapy.